Use of a data gathering toolbox is spurring policy and animal health actions to control and eradicate peste des petits ruminants in East and West Africa - CGIAR Research Program on Livestock (2021)
A data gathering suite of tools created by the International Livestock Research Institute and partners have generated important epidemiological and socio-economic data to inform the control of peste des petits ruminants (PPR) in countries across East and West Africa. The tools, which have been adopted by researchers and National Research Institutes in Ethiopia, Kenya, Tanzania, Senegal, Mali, Burkina Faso and Uganda, are contributing to global PPR eradication efforts aimed at protecting the livelihoods of millions of small ruminant livestock farmers.